Kyai Achjat Irsjad Membangun Organisasi Politik dan Dakwah di Banyuwangi Tahun 1944-1963 - Moch Sholeh Pratama; Ikhsan Rosyid Mujahidul Anwari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STI. Blambangan Banyuwangi, 2021)
Abstract This paper examines the biography of Kyai Achjat Irsjad during his leadership in initiating and directing the NU Blambangan in 1944-1963. Kyai Achjat Irsjad's decision to establish the NU Blambangan was intended for the development of NU in the southern Banyuwangi. This study specifically writes about the arena of character, spiritual, and intellectual forging of Kyai Achjat Irsjad within the family, Islamic boarding schools and NU organizations. From the forging arena, Kyai Achjat Irsjad played a progressive role as a social, political and religious activist in Banyuwangi. The method used in this research is the Historical Method. The research data obtained from the Pegon Community, the memories of Kyai Achjat Irsjad's children, as well as supporting data in the form of scientific works. The results of the study found that Kyai Achjat Irsjad played an important role, some of which were in increasing access to education, performing the first edition of the Qur'an at the Indonesian Ministry of Religion, and strengthening the existence and influence of NU in southern Banyuwangi in the community.